The ingredients of successful adaptive programming in Tanzania: A QCA analysis - Tim Kelsall; Ed Laws; Barbara Befani (Overseas Development Institute (ODI), 2021)
Adaptive management' and 'politically smart programming' are increasingly popular ideas in development. They capture an ambition to programme in ways that are more flexible and experimental, and which respond to and capitalise on political dynamics and incentives. Over the last 10 to 15 years there has been a notable increase in aid programmes that explicitly reference these terms, or similar ideas such as 'doing development differently' and problem-driven iterative adaptation. There is a growing consensus that interventions are more likely to make a positive difference in highly complex situations if they adopt these principles and methods. However, according to recent reviews of the literature on thinking and working politically and adaptive management, much of the evidence used so far to support these approaches is anecdotal, does not meet high standards for robustness, is not comparative and draws on a small number of self-selected, relatively well-known success stories. To generate lessons to help deepen the evidence base, this report uses Qualitative Comparative Analysis (QCA) to explore the most important ingredients of success in the Institutions for Inclusive Development (I4ID) Programme - an adaptive, issue-based governance initiative in Tanzania.
Keywords: 330; Tanzania; Monitoring; evaluation and learning; Adaptation; Governance